Obesity impacts the mechanical response and biochemical composition of patellofemoral cartilage: An in vivo, MRI-based investigation. (March 2022) - Tamayo, K.S.; Heckelman, L.N.; Spritzer, C.E.; DeFrate, L.E.; Collins, A.T.
Abstract: Obesity is a primary risk factor for osteoarthritis. While previous work has addressed relationships between in vivo cartilage mechanics, composition, and obesity in the tibiofemoral joint, there is limited information on these relationships in the patellofemoral joint. The purpose of this study was to compare the patellofemoral cartilage mechanical response to walking in participants with normal and obese body mass indices (BMIs). Additionally, patellar cartilage T1rho relaxation times were measured before exercise to characterize the biochemical composition of the tissue. Fifteen participants (eight with normal BMI and seven with obese BMI) underwent baseline magnetic resonance imaging (MRI) of their right knee. They then walked on a treadmill for 20 min at a speed normalized to their leg length before a second MRI scan. Subsequently, three-dimensional models of the bones and articular surfaces of the patellofemoral joint were created via manual segmentation of the pre- and post-exercise MR images to compute cartilage thickness and strain. Strain was defined as the change in patellofemoral cartilage thickness normalized to the baseline thickness. Results showed that participants with an obese BMI exhibited significantly increased patellofemoral cartilage strain compared to those with a normal BMI (5.4 ± 4% vs. 1.7 ± 3%, respectively; p = 0.003). Furthermore, patellar cartilage T1rho values were significantly higher in participants with obese versus normal BMIs (95 ms vs. 83 ms, respectively; p = 0.049), indicative of decreased proteoglycan content in those with an obese BMI. In summary, the altered patellofemoral cartilage strain and composition observed in those with an obese BMI may be indicative of cartilage degeneration.